Implementation of the Regulation of the Minister of Trade of the Republic of Indonesia Number 07 of 2020 and the Mashlahah Concept in the Phenomenon of Fluctuations in Chicken Egg Prices During the Covid-19 Pandemic - Della Ersya Aprilia; Faishal Agil Al Munawar (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Covid-19 virus that came to Indonesia in early 2020 was able to make many economic sectors, especially trade, experience adverse consequences for the community these economic activists, as in the livestock sector, as chicken eggs which, were disrupted and experienced significant losses. This study aims to mention the impact of fluctuations in chicken egg prices on farmers from the perspective of the Regulation of the Minister of Trade of the Republic of Indonesia number 07 of 2020 and explain the concept of Maslahah in Islamic fiqh related to fluctuations in the price of chicken eggs that occur in Indonesia. Research methods used qualitative research with descriptive analysis. The results of this study show that (1) The response of egg farmers in Turirejo Lawang Village regarding the impact of the Regulation of the Minister of Trade of the Republic of Indonesia Number 07 of 2020 is relatively the same, namely feeling happy because for them this is quite profitable and helpful for farmers even though some expect other more significant steps. (2) The concept of Maslahah in the Regulation of the Minister of Trade of the Republic of Indonesia Number 07 of 2020 by the Government of Indonesia is Maslahah Al-'Ammah, which is the public interest that has an impact on the interests of the people, where general profit does not mean the profit of all, but the profit of most humans and maslahah al-hajiyyah, which, is to complement the previous main advantage in the form of maintenance and facilities for maintenance.